2009
DOI: 10.1371/journal.ppat.1000442
|View full text |Cite
|
Sign up to set email alerts
|

CAR-Associated Vesicular Transport of an Adenovirus in Motor Neuron Axons

Abstract: Axonal transport is responsible for the movement of signals and cargo between nerve termini and cell bodies. Pathogens also exploit this pathway to enter and exit the central nervous system. In this study, we characterised the binding, endocytosis and axonal transport of an adenovirus (CAV-2) that preferentially infects neurons. Using biochemical, cell biology, genetic, ultrastructural and live-cell imaging approaches, we show that interaction with the neuronal membrane correlates with coxsackievirus and adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
131
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(150 citation statements)
references
References 65 publications
13
131
1
5
Order By: Relevance
“…Although we cannot distinguish between endogenous or virusmediated upregulation in Ngb expression within the striatum, we can postulate that after tMCAO transduction profiles may differ or that there is an active transport process occurring similar to what has previously been described with CAV-2 vectors. 36 Previous studies determining the neuroprotective effect of Ngb in vivo showed Ngb-overexpressing transgenic mice had lower levels of lipid peroxidation measured by MDA assay in the ipsilateral hemisphere after tMCAO. 11 In addition, reduced numbers of TUNEL (terminal deoxynucleotidyl transferase dUTP nick end labeling)-positive cells and increased numbers of neurones with a normal morphology (from cresyl violet histology) were seen after delivery of Ngb linked to a fusion protein before tMCAO in C57BL/6J mice.…”
Section: Discussionmentioning
confidence: 97%
“…Although we cannot distinguish between endogenous or virusmediated upregulation in Ngb expression within the striatum, we can postulate that after tMCAO transduction profiles may differ or that there is an active transport process occurring similar to what has previously been described with CAV-2 vectors. 36 Previous studies determining the neuroprotective effect of Ngb in vivo showed Ngb-overexpressing transgenic mice had lower levels of lipid peroxidation measured by MDA assay in the ipsilateral hemisphere after tMCAO. 11 In addition, reduced numbers of TUNEL (terminal deoxynucleotidyl transferase dUTP nick end labeling)-positive cells and increased numbers of neurones with a normal morphology (from cresyl violet histology) were seen after delivery of Ngb linked to a fusion protein before tMCAO in C57BL/6J mice.…”
Section: Discussionmentioning
confidence: 97%
“…Эти фундаментальные различия взаимодейс-твия вирус -хозяин лежат в основе патогенеза многих вирусных инфекций. В нейронах после инвазии боль-шинство вирионов остаются внутри эндоцитозной везикулы, и в таком виде по механизму ретроградного транспорта перемещаются вдоль микротрубочек к телу клетки с использованием динеинов -моторных белков [42][43][44]. Микротрубочки ориентированы (+) -на периферии клетки или аксона и (−) -в направ-лении к телу клетки [45].…”
Section: Ukrainianunclassified
“…These data led to the conclusion that HAdV-C5 internalization is mediated by integrins via the engagement of the conserved RGD motif in the AdV penton (4,11,12). Interestingly, CAR is coendocytosed upon engagement of the canine adenovirus type 2 (CAdV-2, commonly referred to as CAV-2) and HAdV-C5 ex vivo in neurons and neuronal cell lines, raising the possibility that CAR actively participates in the endocytosis of some viruses (13,14). CAV-2 vectors are powerful tools for gene transfer to the brain because they preferentially transduce neurons and undergo efficient axonal retrograde transport (15-18).…”
Section: Importancementioning
confidence: 99%